Impact of the Merger on Bank Syariah Indonesia’s Financial Performance: A Comparative Analysis of Income Structure (2020–2023) - Racmatullah Rusli (Journal of Strategic Innovation in Economics and Business, 2025)
This study examines the financial performance of Bank Syariah Indonesia (BSI) following the strategic merger of three state-owned Islamic banks in 2021, focusing on shifts in income structure across key Islamic financing instruments. Through a comparative analysis of pre-merger (2020) and post-merger (2021–2023) financial reports, we evaluate changes in revenue streams, including murabaha (cost-plus sale), mudharabah (profit-sharing), ijarah (leasing), and operational income. Results indicate a 26.27% increase in murabaha income and 17.6% growth in operational income post-merger, alongside a temporary 22% decline in ijarah revenue during integration. The findings highlight enhanced economies of scale and portfolio diversification achieved through merger-driven consolidation, while identifying challenges in harmonising legacy product lines. This analysis provides critical insights for policymakers and Islamic financial institutions navigating post-merger optimisation strategies.